GLP-1 analogue liraglutide as adjunct treatment in diabetes type 2 after failed bariatric/metabolic surgery - Hellström, Per M. (Annals of Translational Medicine, 2019)
Obesity with its negative effect on health (1) has become a major challenge to physicians as well as surgeons throughout the world. Today more than 650 million people worldwide are obese (1). To the physician, the individuals’ positive energy balance with a greater energy intake than expenditure means an increased rate of diabetes type 2 and insulin resistance along with debilitating complications such as hypertension, stroke and cardiac disease, sleep respiratory disorders including sleep disturbance, blood lipid abnormalities and non-alcoholic fatty liver disease. To the surgeon, the problem mainly deals with the stigmatizing body composition, excessive accumulation of adipose tissue and immobility. Furthermore, there is a link to a number of cancers, such as endometrium, breast, ovary, prostate, liver, gallbladder, kidney, and colorectal cancer.